A study on the prevalence of maxillary mid-line diastema among filipino children aged 6-14 - Baula, Gemma V.
The objectives of this study are: To study the prevalence of the maxillary mid-line diastema in a group of Filipinos - children ages 6-14 years: To prove that the maxillary mid-line diastema closes upon eruption of the canines and to prove that the "ugly duckling" feature of anterior spacing is a natural phenomenon, a transitory period which will subsequently close and to be considered as a form of malocclusion. This study was conducted in one particular school - the Paco Catholic School for reasons as it is a coed school with a large population of 6,000 offering enough subjects. Its concluded that the result of this study parallels that of other investigators that the mid-line diastema at age 6-8 is a transitory developmental phase which gradually disappears with age and subsequent eruption of the canines.